MENINGKATKAN MOTIVASI BELAJAR SENAM LANTAI MELALUI PEMANASAN BERBENTUK PERMAINAN - Vicki Saputra Vicki; Andika Triansyah; Novi Yanti; Mimi Haetami; M. Fachrurrozi Bafadal (Universitas Tadulako, 2023)
Learning motivation will affect student learning outcomes. Students will be interested in learning if what is learned is fun and the benefits are known. learning outcomes. The purpose of this research is to increase motivation to learn floor gymnastics. The type of research used in research is classroom action research. The research subjects totaled 33 students, there were 19 women and 14 men. The research instrument used to measure motivation is the learning motivation questionnaire. The results obtained in Cycle I were as much as 54% which increased and in Cycle II as much as 81%. Based on the results of the discussion of research data on increasing motivation to learn floor gymnastics through heating in the form of games, the researchers concluded that there was an increase in motivation to learn floor gymnastics using a warm-up learning model in the form of games for students at SMPN 21 Pontianak..